An Analysis of Affect in Tabligh Communication in the Digital Era: Ustadz Abdul Somad’s Sermons on the YouTube Platform - Muhamad Febriansyah; Nasichah N; Dwisya Ayu Wanthy Syabdilla; Artika Elfarianti (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study provides an in-depth understanding of the affective dimension of da’wah communication in the digital era. Against the backdrop of technological development, da’wah is no longer confined to conventional methods but has evolved into a more interactive and responsive multi-directional form of communication. Preachers (da’i) now adopt various strategies to enhance the effectiveness of da’wah in the digital sphere. The findings highlight the affective aspects of da’wah communication through a digital platform, namely YouTube. This study takes da’wah content by Ustadz Abdul Somad (UAS) as a sample, as it represents a successful example of reaching audiences through digital channels. Several strategies for enhancing da’wah in the digital era are identified, including mastering various digital platforms, developing storytelling skills, understanding audience online trends and habits, collaborating with digital content creators, implementing interactive technologies, optimizing searchability and online visibility, and maintaining consistent branding and messaging. In conclusion, the utilization of digital technology can create da’wah content that is more dynamic, relevant, and easily accessible to audiences increasingly connected through technology. Thus, this study offers practical guidance for preachers and researchers to enhance the affective impact of da’wah in the digital era, making da’wah more effective and relevant in responding to the dynamics of contemporary communication technology developments.